PENGAWASAN PEMBANGUNAN DESA SUKAMAJU KECAMATAN TELLULIMPOE KABUPATEN SINJAI - Khair, Rijalul; Muhammadiah, Muhammadiah; Parawu, Hafiz Elfiansyah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
The aim of this research is to examine the role of the Village Consultative Body (BPD) in overseeing the development of Sukamaju Village, Tellulimpoe District, Sinjai Regency, focusing on the role of the Village Consultative Body in Development Oversight, with three indicators: setting standards, conducting assessments, and implementing corrective actions. This is a qualitative study. Data collection techniques include observation, interviews, and documentation. Data analysis follows a descriptive model comprising data reduction, data presentation, and conclusion drawing. Data validation is conducted through source triangulation, technique triangulation, and time triangulation. The results of this research found that the role of the village consultative body (BPD) in supervising the development of Sukamaju Village, Tellulimpoe District, Sinjai Regency has been successful, but there needs to be more maximum effort from both the village head and village officials. Development activities have several obstacles, namely the lack of community participation. This research was carried out by conducting direct interviews with informants and documentation with several informants to answer the problem formulation consisting of setting standards, conducting assessments, taking corrective action.